ChemInform Abstract: Conformational Problem of Alkanes in Liquid Crystals by NMR Spectroscopy: A Mini‐Review. Issue 48 (2nd December 2014) - Weber, Adrian C. J.; Chen, Daniel H. J.
Abstract Review: 40 refs.